Moisture content of wood: influence on mechanical behaviour of wood filled impact limiters and importance for quality surveillance during manufacturing. (December 2012) - Eisenacher, G; Kuschke, C; Schubert, S; Neumann, M; Sterthaus, J; Nitz, T; Wille, F
Abstract : The moisture content of wood is known to have a significant influence on the wood's mechanical properties. Using wood as an energy absorber in impact limiters of packages for the transport of radioactive material, it is of particular importance to ensure the moisture content and thus relevant mechanical properties to be in specified limits. The paper surveys the influence of wood moisture content on the mechanical properties of wood. Different measuring methods are discussed with respect to in situ applicability, accuracy and effort. The results of an experimental analysis of the accuracy of hand held moisture metres using the electrical resistance method are discussed. Conclusions are drawn regarding the measurement of moisture content of wood upon delivery as well as of complete impact limiter assemblies. Requirements for quality surveillance during manufacturing of wood filled impact limiters are derived and it is exemplified how to meet them. Construction, manufacturing and inspection of impact limiter encapsulation with regard to leak tightness are addressed.